2018
DOI: 10.1007/s12161-018-1193-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evaluation of Poultry Meat Shelf Life Using PTR-MS

Abstract: The use of proton transfer reaction mass spectrometry (PTR-MS) for freshness classification of chicken and turkey meat samples was investigated. A number of volatile organic compounds (VOCs) were selected based on the correlation (> 95%) of their concentration during storage at 4°C over a period of 5 days with the results of the microbial analysis. In order to verify if the selected compounds are not sample-specific, a number of samples sourced from various retailers were classified using the concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Based on the DLLME-GC-MS analysis it can be observed that the marked increase of the BAI value after the second day of refrigerated storage is mostly due to the increased concentration of cadaverine. The appearance of poultry meat spoilage indicators after the second day of refrigerated storage is supported by both sensory analysis [24] and bacteriological analysis [31], and also corroborates with the results obtained earlier using the same method [29]. Although in the referenced study the samples were stored under slightly different conditions (different containers).…”
Section: Resultssupporting
confidence: 86%
“…Based on the DLLME-GC-MS analysis it can be observed that the marked increase of the BAI value after the second day of refrigerated storage is mostly due to the increased concentration of cadaverine. The appearance of poultry meat spoilage indicators after the second day of refrigerated storage is supported by both sensory analysis [24] and bacteriological analysis [31], and also corroborates with the results obtained earlier using the same method [29]. Although in the referenced study the samples were stored under slightly different conditions (different containers).…”
Section: Resultssupporting
confidence: 86%
“…The deterioration of perishable foods during storage is intimately connected with the growth of undesired microbes, a field of investigation that found valuable applications for PTR-based analytical strategies (e.g. [82] ).…”
Section: Bioprocess Monitoringmentioning
confidence: 99%
“…freshness, adulteration, quality classification) (for an overview see: Ellis & Mayhew, 2014). Some of the most recent PTR-MS applications examples are in saffron (Nenadis, Heenan, Tsimidou, & Van Ruth, 2016) and anhydrous milk fat (Pedrotti et al, 2018(Pedrotti et al, , 2020 quality control, for evaluating shelf life of poultry meat (Wojnowski et al, 2018) and lactose free milk (Bottiroli et al, 2020) and for botanical and geographical origins characterization of both cocoa (Acierno, Yener, Alewijn, Biasioli, & Van Ruth, 2016) and coffee beans (Yener et al, 2014(Yener et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%